Green synthesis of TiO2 nanoparticles from Syzygium cumini extract for photo-catalytic removal of lead (Pb) in explosive industrial wastewater - Sethy, Naresh Kumar; Arif, Zeenat; Mishra, Pradeep Kumar; Kumar, Pradeep (Green processing and synthesis, 2020)
Green synthesis is a simple, non-toxic, economical and eco-friendly approach for the synthesis of nanoparticles. In the present work, nanoparticles of titanium dioxide (TiO NPs) were synthesized using an aqueous solution of leaf extract as a capping agent. These green synthesized TiO NPs were further evaluated for photo catalytic removal of lead from industrial wastewater. Obtained nanoparticles were characterized using: high-resolution scanning electron microscopy (HRSEM), high-resolution transmission electron microscopy (HRTEM), X-ray energy dispersive spectroscopy (EDS), Fourier transform infrared (FT-IR) spectroscopy, X-ray diffraction (XRD), dynamic light scattering (DLS) and Brunauer-Emmett-Teller (BET). Obtained results revealed that synthesized TiO NPs possess spherical morphology with anatase phase with a large BET surface area of 105 m /g. Photo catalytic studies of TiO NPs for lead removal from explosive wastewater were performed in a self-designed reactor. Inductive coupled plasma spectroscopy (ICP) was used to determine the lead concentration. Obtained results witnessed 75.5% removal in chemical oxygen demand (COD) and 82.53% removal in lead (Pb ). This application of green TiO NPs is being explored for the first time.